Humic field biostimulation as a sustainable agricultural practice to increase yield of main grains: evidence from on-farm trials - Izquierdo, Juan; Arriagada, Osvin; García-Pintos, Gustavo; Ortiz, Rodomiro; García-Pintos, Martín; García-Pintos, Marcelo (Frontiers in Plant Science, 2025)
IntroductionConventional agriculture relies heavily on synthetic fertilizers and pesticides, raising questions regarding its long-term sustainability. The use of biostimulants is an environmentally friendly approach to improving crop yields. However, most of these results have been obtained under controlled conditions, making it necessary to evaluate them under commercial production conditions. Therefore, this study aimed to assess the effect of a single foliar spray of a humic biostimulant (HB) on the yield and profitability of five main crops.Methods448 On-farm strip trials (OFT) were conducted on commercial farms from 2014 to 2024 in the main production zones of Uruguay. The HB was applied at a critical stage of the growth cycle in soybean (R3–R4), rice (V5–V9), maize (V6), wheat (Z1.6), and barley (Z1.6). Yield responses and net economic returns were measured for each crop.Results and discussionThe HB increased the average yield of all five crops. The overall mean yield response was significant, ranging from 7.6% to 15.7% for rice and maize, respectively. In barley, HB showed greater effectiveness at lower-yielding sites, reaching 4 t ha−1. In rice, a tendency towards a greater impact on low- and high-yield OFTs was observed. In contrast, HB had a relatively constant effect on maize, wheat, and soybeans. Based on empirical data (normal scenario), the net economic returns varied from US 85.1 to 122.0 ha−1 for wheat and maize, respectively. The probability of exceeding the break-even cost ranged from 83.4% to 89.1% for soybean and wheat, respectively. To our knowledge, this is the first study to demonstrate that a single foliar application of HB at a critical stage of development increases crop yield and profitability for farmers under OFT conditions over several years and at multiple sites. Therefore, this practice can be applied by Uruguayan farmers to sustainably increase yields and economic profits.